Active Warming Utilizing Combined IV Fluid and Forced-Air Warming Decreases Hypothermia and Improves Maternal Comfort During Cesarean Delivery: A Randomized Control Trial. (May 2016) - Cobb, Benjamin; Cho, Yuri; Hilton, Gillian; Ting, Vicki; Carvalho, Brendan
Abstract : BACKGROUND: The aim of this study was to apply both IV fluid and forced-air warming to decrease perioperative hypothermia in women undergoing cesarean delivery with spinal anesthesia. The authors hypothesize that combined-modality active warming (AW) would increase maternal temperature on arrival at the postanesthesia care unit (PACU) and decrease the incidence of maternal perioperative hypothermia (<36°C) compared with no AW. METHODS: Forty-six healthy women ( n = 23 per group) undergoing scheduled cesarean delivery with spinal anesthesia (10–12 mg bupivacaine + 10 μg fentanyl) were enrolled in this double-blinded, randomized controlled trial. Women were randomly assigned to receive either AW (warmed IV fluid and lower body forced-air warmer) or no warming (NW; blankets only). SpotOn TM Monitoring System was used to measure core temperature intraoperatively and for 1 hour postoperatively. The primary outcome measure was maternal temperature on arrival at the PACU. Secondary outcome measures included incidence of maternal perioperative hypothermia (<36°C), incidence of shivering, thermal comfort scores (0–100 scale), Apgar scores, and umbilical cord blood gas analysis. RESULTS: Demographic, obstetric, and surgical data were similar between study groups. The AW group (35.9°C ± 0.5°C) had a significantly higher temperature on arrival at the PACU compared with the NW group (35.5°C ± 0.5°C, P = 0.006; 95% confidence interval of mean difference, 0.1°C–0.7°C). Fourteen (64%) women in the AW group and 20 (91%) in the NW group were hypothermic during the study period ( P = 0.031). Median (interquartile range) thermal comfort scores were 100 (95–100) in the AW group and 90 (70–100) in the NW group ( P = 0.008). There were no significant differences in the incidence of intraoperative shivering (22% in the AW and 45% in the NW groups; P = 0.11), Apgar scores, or umbilical vein blood gas values between the study groups. CONCLUSIONS: Fluid combined with forced-air warming is effective in decreasing the incidence of perioperative hypothermia and improving maternal thermal comfort. However, despite multimodal AW, the majority of women became hypothermic, and shivering was not prevented. The findings suggest that combined AW for cesarean delivery with spinal anesthesia is difficult, and only modest benefit should be expected. Abstract : Published ahead of print February 18, 2016